2001
DOI: 10.1002/cne.1312
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of glial cells and motor neurons during the formation of neuromuscular junctions in cocultures of rat spinal cord explant and human muscle

Abstract: Motor axons extending from embryonic rat spinal cord explants form fully mature neuromuscular junctions with cocultured human muscle. This degree of maturation is not observed in muscle innervated by dissociated motor neurons. Glial cells present in the spinal cord explants seem to be, besides remaining interneurons, the major difference between the two culture systems. In light of this observation and the well documented role of glia in neuronal development, it can be hypothesized that differentiated and long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 35 publications
3
39
0
Order By: Relevance
“…A similar synaptogenic effect of mammalian Schwann cells has been reported in mammalian motoneuron cultures (Ullian et al, 2004), as well as in rat motoneuron and human muscle fiber cocultures (Guettier-Sigrist et al, 2000;Mars et al, 2001). It would be intriguing to test whether these synaptogenic effects of Schwann cells are also mediated by TGF-␤1.…”
Section: Possible Roles Of Tgf-␤1 In the Development Of Nmjs In Vivosupporting
confidence: 62%
“…A similar synaptogenic effect of mammalian Schwann cells has been reported in mammalian motoneuron cultures (Ullian et al, 2004), as well as in rat motoneuron and human muscle fiber cocultures (Guettier-Sigrist et al, 2000;Mars et al, 2001). It would be intriguing to test whether these synaptogenic effects of Schwann cells are also mediated by TGF-␤1.…”
Section: Possible Roles Of Tgf-␤1 In the Development Of Nmjs In Vivosupporting
confidence: 62%
“…In the present study we used an in vitro system in which motor axons extending from embryonic rat spinal cord explants functionally innervate co-cultured human muscle. Under such conditions a high degree of differentiation of the human skeletal muscle fibres is obtained that is never observed in aneural human muscle [1,6].…”
Section: Introductionmentioning
confidence: 92%
“…Cells expressed green fluorescent protein (GFP) under the control of the post-mitotic MN-specific Hb9 promoter (Supplementary Figure S3a); thus, we could visually confirm differentiation of MNs without the addition of exogenous factors or antibodies. Fluorescent imaging revealed that EBs also contained proliferating glia (Figure 2c), which are known to contribute to the formation and maintenance of the NMJ and differentiation and survival of MNs 11 .…”
Section: Differentiation Of Ebs Containing Mnsmentioning
confidence: 99%
“…Early research on the formation of NMJs in two dimensions (2D) has primarily focused on either the co-culture of excised or isolated muscle and neural tissues in vitro 11,12 , or the differentiation of mouse [13][14][15][16] or human [17][18][19] embryonic stem cells into MNs (usually through the formation of embryoid bodies or EBs), which were then co-cultured with excised or engineered muscle tissues. Beyond applications in regenerative medicine and therapeutics 20 , however, only a few studies have produced 3D NMJ platforms or applied neuromuscular research to living cellular systems using embryonic or neural stem cells [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%